Makna Teologis Menjatuhkan Tanah dan Menaburkan Bunga di Atas Peti Mati Pada Upacara Pemakaman - Desnia Agus Berlian Hulu; Dominikus Doni Ola (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This writing is backgrounded beset by the reality of the situation of people who do not understand the theological meaning of dropping soil and scattering flowers on the coffin at the funeral ceremony. This is caused by the people's lack of knowledge and lack of assistance to the people. The purpose of this writing is so that people can understand the theological meaning of dropping soil and scattering flowers on the coffin at a funeral ceremony. The method used in this writing is literature review, namely examining the theme of this writing by utilizing ideas and understanding from books, Church documents and other knowledge. The results of this writing are first, that the theological meaning of dropping the ground reminds us that humans come from the ground and will return to the ground. Meanwhile, scattering flowers is a means of expression and a symbol of the eternal beauty of life. Second, the people understand and understand the theological meaning of dropping soil and scattering flowers on the coffin at the funeral ceremony.